2011
DOI: 10.1161/strokeaha.110.607200
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Mediates Endogenous Protection Against Subarachnoid Hemorrhage-Induced Cerebral Vasospasm

Abstract: Background Vasospasm-induced delayed cerebral ischemia (DCI) remains a major source of morbidity in patients with aneurysmal subarachnoid hemorrhage (SAH). We hypothesized that activating innate neurovascular protective mechanisms by preconditioning (PC) may represent a novel therapeutic approach against SAH-induced vasospasm and neurological deficits; and secondarily, that the neurovascular protection it provides is mediated by endothelial nitric oxide synthase (eNOS). Methods Wild type (WT) mice were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 36 publications
3
81
0
Order By: Relevance
“…In vitro, EPCs can differentiated into endothelial lineage cells, and in animal models of ischemia, EPCs are shown to incorporate into sites of active neovascularization [10,11,12]. Endothelial nitric oxide synthase (eNOS) and its bioactive product nitric oxide (NO) are well-established proangiogenic molecules [13]. eNOS-derived NO regulates cardiac myocyte function, myocardial neovascularization, and myocardial perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, EPCs can differentiated into endothelial lineage cells, and in animal models of ischemia, EPCs are shown to incorporate into sites of active neovascularization [10,11,12]. Endothelial nitric oxide synthase (eNOS) and its bioactive product nitric oxide (NO) are well-established proangiogenic molecules [13]. eNOS-derived NO regulates cardiac myocyte function, myocardial neovascularization, and myocardial perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…19,27 Decreased functionality of this pathway following SAH has been linked to the pathophysiology of DCI including CVS. 58,69,71,77,85 Studies investigating the eNOS-NO-cGMP pathway have shown that inhibition of PDE-V has substantial beneficial effects. In animal SAH studies, PDE-V inhibition (mainly via administration of sildenafil, an FDA-approved selective PDE-V inhibitor) acutely reverses SAH-induced CVS, 2,28,31,32,34,42 reduces neuronal cell death, 32 restores impaired autoregulatory mechanisms, 73 and improves neurological outcomes.…”
mentioning
confidence: 99%
“…Inducible NOS (iNOS) was found to be involved in isoflurane PC-induced neuroprotection in in vivo and in vitro conditions, as well as during IPC [16,63,64]. eNOS has been recently implicated as a mediator of neurovascular protection against subarachnoid hemorrhage (SAH)-induced vasospasm, through HPC in mice, showing for the first time that PC is beneficial for other forms of stroke as well [65].…”
Section: Nitric Oxide (No) Synthasementioning
confidence: 99%